Medicine in Ancient Assur A Microhistorical Study of the Neo-Assyrian Healer Kiṣir-Aššur - Arbøll, Troels Pank (Ancient Magic and Divination, 2021)
In Medicine in Ancient Assur Troels Pank Arbøll offfers a microhistorical study of a single exorcist named Kiṣir-Aššur who practiced medical and magical healing in the ancient city of Assur (modern northern Iraq) in the 7th century BCE. The book provides the first detailed analysis of a healer's education and practice in ancient Mesopotamia based on at least 73 texts assigned to specific stages of his career. by drawing on a microhistorical framework, the study aims at significantly improving our understanding of the functional aspects of texts in their specialist environment. Furthermore, the work situates Kiṣir-Aššur as one of the earliest healers in world history for whom we have such details pertaining to his career originating from his own time. Readership: Suited for everyone interested in ancient Near Eastern magico-medical texts and practices, ancient libraries, and the training of specialists, as well as anyone concerned with the history of ancient medicine.